2015
DOI: 10.1371/journal.pone.0122238
|View full text |Cite
|
Sign up to set email alerts
|

Topical Olive Oil Is Not Inferior to Hyperoxygenated Fatty Aids to Prevent Pressure Ulcers in High-Risk Immobilised Patients in Home Care. Results of a Multicentre Randomised Triple-Blind Controlled Non-Inferiority Trial

Abstract: Pressure ulcers represent a major current health problem and produce an important economic impact on the healthcare system. Most of studies to prevent pressure ulcers have been carried out in hospital contexts, with respect to the use of hyperoxygenated fatty acids and to date, no studies have specifically examined the use of olive oil-based substances.Methods and Design Main objective: To assess the effectiveness of the use of olive oil, comparing it with hyperoxygenated fatty acids, for immobilised home-care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 25 publications
2
19
0
3
Order By: Relevance
“…Our final results corroborate the preliminary data obtained in the intermediate analysis . They are also in agreement with the findings of another Spanish research group, who found that an olive oil product and HOFA product were equally effective to prevent PUs in 831 at‐risk patients receiving home care in the province of Malaga …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our final results corroborate the preliminary data obtained in the intermediate analysis . They are also in agreement with the findings of another Spanish research group, who found that an olive oil product and HOFA product were equally effective to prevent PUs in 831 at‐risk patients receiving home care in the province of Malaga …”
Section: Discussionsupporting
confidence: 90%
“…The present results demonstrate that the therapeutic safety profile of topical treatment with olive oil is equivalent to that of HOFA treatments. No adverse effects were observed in our olive oil group, similar to findings of other studies on the topical application of olive oil on healthy skin and diabetic foot ulcers . Olive oil can therefore be considered a safe product for topical application.…”
Section: Discussionsupporting
confidence: 90%
“…In the between‐groups analysis, conducted at the end of the follow‐up period, per protocol, none of the body areas evaluated presented risk differences for pressure ulcer incidence that exceeded the pre‐established 10% delta value. The intention‐to‐treat analysis showed that the lower limit of the confidence interval established for noninferiority was not exceeded in any of the areas assessed …”
Section: Resultsmentioning
confidence: 99%
“…By means of a multicenter randomized triple‐blind controlled non‐inferiority trial, we evaluated the noninferiority of virgin extra olive oil vs. HOFA. The results obtained show that none of the body areas evaluated presented risk differences for pressure ulcer incidence that exceeded the pre‐established 10% delta value . However, despite these promising clinical results, to date no information has been published concerning the cost implications of such an intervention.…”
mentioning
confidence: 80%
See 1 more Smart Citation